Investigation of structural dynamics of substances using ultrafast electron diffraction and microscopy: (50th anniversary of the Institute of Spectroscopy, Russian Academy of Sciences). (March 2019) - Aseyev, S A; Ryabov, E A
Abstract: The structural dynamics of matter, induced by powerful and most often femtosecond laser pulses, is manifested in an atomic-molecular 'movie', a collection of processes, the exploration of which is of immense interest for today's natural sciences. Studying this global phenomenon requires an ultra-high spatio-temporal resolution that involves the development of dedicated research methods. Laser spectroscopy may be applied to determine energy states of samples and track their evolution in time; however, the structural dynamics of matter can only be disclosed from that information by indirect methods. We present here direct techniques for studying laser-perturbed substances in the spatio-temporal continuum where matter is probed with ultrashort electron and X-ray pulses. We also describe the first series of experiments performed with the aid of a femtosecond electron diffractometer and picosecond transmission electron microscope at the Institute of Spectroscopy of the Russian Academy of Sciences based in Troitsk, Moscow.